IMPROVING STUDENTS MASTERY OF VOCABULARY THROUGH THE USE OF GLOSSING TECHNIQUE - Mamaghe, Niveyla; Rombepajung, Paula; Hampp, Paula (Journal of English Culture, Language, Literature and Education, 2020)
The aim of the research is to improve the students vocabulary through the use of Glossing technique The design of this research is quantitative research through pre experimental design with pre test and post test design This study was conducted at SMP Anugrah Tondano The subject of the research was the second grade students in academic year of 2019 2020 The writer used reading text of Narrative text The result of the data analysis showed that there was an increase between the pre test and post test It can be seen from 10 students showed that the mean score of pre test was 53 and post test was 74 score Based on this finding from this study it can be concluded that having more vocabulary significantly affects the comprehension of the students reading activity Moreover by having many vocabularies the students can easily get the information and can enrich their knowledge by reading a lot of book Finally this research proved that theGlossing technique effective to improve student s vocabulary in reading comprehension < p>